A Ciência Biomédica e o processo cvilizador - Farias, Bruna de; Sandalowski, Mari Cleise (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
This article aims to understand the biomedical practices, from an analysis of science, especially focused on the dichotomy fact and value. Therefore, the text refers to a questioning of the idea of neutrality, while scientific precept front of the evaluative questions that biomedical science produces in society. For this, outside incorporated the idea of “civilizing process” of Norbert Elias, as an analytical tool for understanding the paradoxical normativity that science has on individuals.